Peningkatan Aktivitas dan Hasil Belajar Bahasa Inggris pada Siswa Kelas XPK 2 Madrasah Aliyah Negeri (MAN) 2 Pesisir Selatan Tahun Ajaran 2020/2021 melalui Pelaksanaan Model Pembelajaran Group Investigation - Risna Aris (Journal on Education, 2023)
This study aims to determine the activities and learning outcomes of class X PK 2 MAN 2 Pesisir Selatan through the implementation of the Group Investigation learning model in English subjects. This type of research uses classroom action research. This research is reflective in nature by increasing classroom learning in a more professional manner. The subjects in this study were 33 students of class XPK 2. Implementation of this study using the "cycle model". This cycle consists of four components, namely (1) planning, (2) action, (3) observation, and (4) reflection. Data collection in the research was carried out by means of discussions, interviews, observations, and tests. The data analysis technique was carried out using descriptive analysis and percentage analysis. The results showed that first, the learning outcomes obtained by students using the Group Investigation learning model increased along with an increase in students' understanding of the material being studied in the teaching and learning process of English subjects. Second, the use of cooperative learning with the Group Investigation learning model type can increase student learning activity and motivation in the teaching and learning process of English subjects. Third, achieving the learning objectives that have been formulated in the Learning Implementation Plan (RPP) in the teaching and learning process of English subjects.